Challenges in tackling environmental concerns in indigenous education in Mexico - Rosa Guadalupe Mendoza-Zuany (Environmental Association of Southern Africa, 2019)
This article analyses the curriculum document called Indigenous language: Curriculum parameters, basic education, indigenous primary, that outlines study programmes for indigenous languages in Mexico, specifically for the Indigenous Language Subject in primary schools prescribed by the General Department of Indigenous Education (DGEI) of the Public Education Secretary (SEP) in 2008. The curriculum document will be analysed for its inclusion of topics and concerns pertaining to the environment, nature, biodiversity and indigenous territories. This analysis is relevant because the Indigenous Language Subject is the only curriculum area that has been designed by indigenous teachers, as part of their struggle to see their languages and cultures placed on a level with Spanish. Two important issues stand out from the analysis. Firstly, the curriculum document recognises community elders and parents as bearers and builders of indigenous knowledge concerning the environment. Second, it recognises that children learn from everyday cultural practices such as farming crops, local food production, etc. However, the analysis also revealed matters of concern, and these should be treated as challenges to be overcome.